Risk and responsibility: Private equity financiers and the US shale revolution. Issue 1 (17th August 2021) - Field, Sean
Abstract : Drawing on ethnographic research in Houston, Texas, I explore how private equity financiers in the US hydrocarbon industry are empowered to define and take financial risks on our collective behalf. The US shale revolution could not have unfolded without the financial risk‐taking activities of private equity financiers who channeled billions of dollars into US unconventional exploration and production ("fracking"). These financiers are motivated not only by their own capitalist projects but also by feelings of responsibility to take financial risks for the benefit of others. Shedding light on this enigmatic community, I attend to the relatively neglected area of hydrocarbon finance and highlight how perceptions of financial risk and responsibility become entangled to shape our collective energy present(s) and future(s). As an essential piece of the financial infrastructure that connects investors around the world with US hydrocarbon activities, I suggest that private equity firms are conduits not only of capital but also of responsibility.